ANALISA KINERJA KEUANGAN KOPERASI DI KUD SUMBER MAKMUR NGANTANG MALANG - Sudjoni, Moch. Noerhadi; Saputro, Arief Joko (MEDIAGRO, 2024)
Financial health performance will determine the progress of the cooperative. The healthier the financial performance, the more advanced and independent the cooperative will be. For this reason, it is necessary to analyze the performance of the financial reports, so that management can make the right decisions for the further development of the cooperative. The success of a cooperative will reflect the qualifications or quality of its financial health performance. The aim of this research is to determine the health performance of the financial reports of KUD Sumber Makmur Ngantang. This research method uses a case study approach. The data collection method is using primary data and secondary data. The research location is KUD Sumber Makmur Ngantang District. Poor. The financial performance analysis period is the balance sheet & profit and loss report for 2021 & 2022. This research uses the "present ratio" as a comparison, namely 1. Liquidity Ratio. 2. Solvency Ratio. 3. Activity Ratio, 4. Profitability Ratio. There are 4 health performance indicators as follows: 1. A score of 3.25 - 4.00, a score of 4 means healthy. 2. A score of 2.50 – 3.24, a score of 3 means quite healthy. 3. A score of 1.5-2.49, a score of 2 means unhealthy. 4. A score of less than 1.5, a score of 4 means unhealthy. The results of this research are an analysis of the financial health performance of KUD Sumber Makmur in 2021 of 2.73 and in 2022 of 2.58 with a standard of 2.50-3.24 which is interpreted as quite healthy. For 2022, the performance value decreased by 2.58 compared to 2021 of 2.73. The suggestions in this research are: 1. To overcome the problem of net profit margin which is still below 1%, close business units that continue to lose money, for example building shop units. 2. Develop businesses that support core businesses, for example tourism education milk & cattle.